Insulin degludec is not associated with a delayed or diminished response to hypoglycaemia compared with insulin glargine in type 1 diabetes: a double-blind randomised crossover study - Koehler, Gerd (Springer Berlin Heidelberg, 2013)
AIMS/HYPOTHESIS: Insulin degludec (Des(B30)LysB29(γ-Glu Nε-hexadecandioyl) human insulin; IDeg) is a new basal insulin with an ultra-long flat action profile. The acute physiological responses to hypoglycaemia with IDeg and insulin glargine (A21Gly,B31Arg,B32Arg human insulin; IGlar) were compared. METHODS: Twenty-eight adult type 1 diabetic patients with normal hypoglycaemia awareness (age = 41 ± 12 years, HbA(1c) = 7.8 ± 0.6% [62.8 ± 7 mmol/mol]) were randomised to once-daily IDeg or IGlar for 5 days in a two-period crossover design. Participants and research staff were blinded to group assignment. Patients were assigned the lowest available randomisation number from a set of blinded randomisation codes provided by the trial sponsor. Hypoglycaemia was induced by administering three times the usual daily insulin dose at midnight on day 5. Plasma glucose (PG) was stabilised by glucose clamp (5.5 mmol/l) for 7–9 h post dosing. Next morning, PG was allowed to decrease stepwise from 5.5 to 3.5 mmol/l (maintained for 30 min) to 2.5 mmol/l (for 15 min). PG was then increased to 3.9 mmol/l (for 120 min), before being returned to baseline. Hypoglycaemic symptom score (HSS), hypoglycaemic awareness, cognitive function, counter-regulatory hormones and vital signs were assessed during each glucose plateau. The primary analysis was to compare IDeg vs IGlar with respect to HSS at nadir PG concentration (2.5 mmol/l). RESULTS: The full analysis set for treatment comparisons comprised data from all 28 exposed patients. Rates of PG decline and PG at nadir were similar for IDeg and IGlar. No treatment differences in HSS (estimated difference: 0.17 [95% CI −1.71, 2.05]; p > 0.05), cognitive function or awareness were observed at any time. Growth hormone and cortisol responses during hypoglycaemia were greater with IDeg than IGlar (AUC treatment ratio [IDeg/IGlar]: 2.44 [1.30, 4.60], p < 0.01; and 1.23 [1.01, 1.50]; p < 0.05), and adrenaline (epinephrine) responses trended higher (1.40 [0.96, 2.04], p = 0.07). The rates of recovery from hypoglycaemia were similar. CONCLUSIONS/INTERPRETATION: IDeg and IGlar elicit comparable symptomatic and cognitive responses to induced hypoglycaemia. IDeg may elicit a moderately greater endocrine response, but times to PG recovery were similar for the two insulins. TRIAL REGISTRATION: ClinicalTrials.gov NCT01002768. FUNDING: Novo Nordisk.